Tactical behaviors in men`s 800-m Olympic and world-championship medalists: A changing of the guard - Sandford, G. N.; Pearson, S.; Allen, S. V.; Malcata, R. M.; Kilding, A. E.; Ross, A.; Laursen, P. B. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess the longitudinal evolution of tactical behaviors used to medal in men`s 800-m Olympic Games (OG) or world-championship (WC) events in the recent competition era (2000-2016). Methods: Thirteen OG and WC events were characterized for 1st- and 2nd-lap splits using available footage from YouTube. Positive pacing strategies were defined as a faster 1st lap. Season`s best 800-m time and world ranking, reflective of an athlete`s "peak condition," were obtained to determine relationships between adopted tactics and physical condition prior to the championships. Seven championship events provided coverage of all medalists to enable determination of average 100-m speed and sector pacing of medalists. Results: From 2011 onward, 800-m OG and WC medalists showed a faster 1st lap by 2.2±1.1 s (mean, ±90% confidence limits; large difference, very likely), contrasting a possibly faster 2nd lap from 2000 to 2009 (0.5, ±0.4 s; moderate difference). A positive pacing strategy was related to a higher world ranking prior to the championships (r=.94, .84-.98; extremely large, most likely). After 2011, the fastest 100-m sector from 800-m OG and WC medalists was faster than before 2009 by 0.5, ±0.2 m/s (large difference, most likely). Conclusions: A secular change in tactical racing behavior appears evident in 800-m championships; since 2011, medalists have largely run faster 1st laps and have faster 100-m sector-speed requirements. This finding may be pertinent for training, tactical preparation, and talent identification of athletes preparing for 800-m running at OGs and WCs. (Attention! registration on the IAAF site is required for downloading)